The Role of Islamic Religious Education (PAI) Teachers in Overcoming Difficulties in Reading the Qur'an among Seventh Grade Students at SMPN 2 Kadindi - Muslim, Mazhabul Khalid; Arifin, Syamsul; Zainudin, Zainudin (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to identify the forms of difficulties in learning to read the Qur'an faced by seventh-grade students at SMPN 2 Kadindi, understand the role of Islamic Religious Education (PAI) teachers in overcoming these difficulties, and identify the factors causing these learning difficulties. The research employs a qualitative approach aimed at revealing factual conditions without manipulation. Data collection techniques include observation, interviews, and documentation. The collected data is then analyzed descriptively and qualitatively. The results show that the forms of difficulties encountered by students in learning to read the Qur'an at SMPN 2 Kadindi include the pronunciation of hijaiyyah letters (makharijul huruf), fluency issues in reading, and lack of understanding of tajweed rules. The role of PAI teachers in overcoming these difficulties involves providing Qur'an reading guidance before lessons start, offering personal guidance, and applying various teaching methods. The factors causing these learning difficulties include low student interest in PAI lessons, family education background, and school policies directing students to read the Qur'an through existing materials or textbooks. The three roles played by PAI teachers at SMPN 2 Kadindi have proven effective in overcoming the difficulties in learning to read the Qur'an, as evidenced by the positive responses from students. However, some students still do not take the lessons seriously. Nonetheless, with the teachers' efforts, students have shown improvements such as better pronunciation of hijaiyyah letters, mastering the length of readings, and reading the Qur'an more fluently, although there is still room for improvement in reading fluency and tajweed comprehension.